Artificial Intelligence Technology and its Implications for the Sovereignty of the Nation-State (The International Journal of Educational Sciences and Arts, 2024)
Artificial intelligence represents one of the tools/means of transformation that has affected the contents of contemporary power, and which has begun to spread greatly as a result of technological-informational progress, specifically in the military-security aspect, and since power has undergone a transition from one type to another type that is completely different from the previous one, it is self-evident That this transformation leads to changes in the military-security field of wars and global security, as it represents a four-way equation of composition and interconnection between the variables of power, security, wars, and conflicts. If the tools of power change, it is reflected in the nature and contents of wars. International unity today no longer faces traditional-classical armies. As it was during the past years, today we find that the tools/methods of war have differed, and obviously we cannot ignore the role of artificial intelligence technology in the strategic-military field, which represents one of the tactical and technical strategies that are used whether by the international unit as the main actor in international relations or by Before the new non-state actors in global politics, the tools and types of power have become available and not limited to the state that possesses them, due to the effects of artificial intelligence on all political, economic, military, security and cultural levels. However, I focus in this research on the military-security aspect as it is one of the aspects that... It is of great importance at the present time, especially since sovereignty is linked to this important strategic aspect.
Keywords: Autonomous Robots; Killer Robots; Artificial Intelligence; Power Shifts; The Problem of Hacking; Sovereignty Drones